The Correlation of Environmental Sanitation with Stunting Incidents in School-Age Children - Ernawati, Rini; Nurjanah, Misbah; Wahyuni, Tri (Indonesian Journal of Global Health Research, 2024)
Stunting in children can be caused by direct and indirect factors, such as environmental sanitation factors. Children who live in an unhealthy environment are prone to illness, which will interfere with growth in children and can lead to stunting. This study aims to determine the relationship between environmental sanitation factors (drinking water sources, latrines, waste disposal, garbage disposal, healthy homes, and air pollution) with the incidence of stunting in school-age children at SD Loa Janan Ilir District, Samarinda City. The research method used an analytic survey with a cross-sectional approach, with a sample of 188 respondents, consisting of parents and first graders from 5 elementary schools. The instruments used were microtoise and questionnaires. Data analysis using chi-square. The results showed that the source of drinking water was p = 0.000, the toilet variable was p = 0.000, the waste disposal variable was p 0.020, the garbage disposal variable was p = 0.000, the healthy house variable was p = 0.003 and the air pollution variable was p = 0.000. All variables have a p-value <0.05, so Ho is rejected, meaning that the variable sources of drinking water, latrines, waste disposal, housing conditions, air pollution are all related to the incidence of stunting in school children. Improving environmental sanitation that meets health requirements is crucial to preventing stunting in school-age children.